Penerapan Teknologi Informasi di Kantor Arsip Perpustakaandan Dokumentasi (KAPD) Kota Padang - Sari, Ivi Nanda; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
Application of information technology in libraries and archives office documentation on padang  city. The Papers Library information science courses and archives. Indonesian language and literature majors area. Faculty of language and art.university state of padang. This study discusses the application of information technology in libraries and archives offices documentation in padang city. This study aimed to : describe the utilization of information in libraries and archives offices documentation in padang city, describe te constrain in application of information technology.  Data ware collected by  means of observation and interviews with librarian. Data analysis is done effectively. Based on data analyst, we can get as follows : the first,application of information technology for librarian in offices documentation in padang City involve  ease of information access and collection of interest  librarian found easily with application of technology information. Second: observing constraints that occur on libraries and archives office documentation on padang  city as follows  :  (a) a few of unit computer,  (b) the facilities are not qualified, (c) librarian are not a expert wear computer so libraria must be get training computer sience and increase sosialisation it for librarian.  The result of study suggest the application of information technologi to impove the library is growing over time. Keywords: application of information technology; librarian